Band discontinuities and local interface composition in BeTe/ZnSe heterostructures - Nagelstraßer, M.; Dröge, H.; Fischer, F.; Litz, T.; Waag, Andreas; Landwehr, G.; Steinrück, Hans-Peter (Journal of Applied Physics, 1998)
Using photoelectron spectroscopy, we have investigated the band alignment at the interface of pseudomorphic BeTe/ZnSe(100) heterojunctions for different interface terminations. The heterostructures of high structural quality have been produced by molecular beam epitaxy; the interface termination was adjusted by variation of the growth parameters between the growth process of ZnSe and BeTe. The valence band offset for a Zn-rich BeTe/ZnSe interface is determined to be 1.26±0.15 eV, for the Se-rich BeTe/ZnSe interface a value of 0.46±0.15 eV is obtained. Our results show that the band alignment can be modified by the interface composition even for isovalent heterostructures. © 1998 American Institute of Physics.